(untitled) (Research, Society and Development, 2021)
Brazil is the largest coffee producer in the world, especially in Minas Gerais, responsible for approximately 50% of the national production of coffee beans. For the implementation of coffee plantations, it is necessary a good planning and technical knowledge of the environmental variables, information that can be obtained with the techniques of geoprocessing, helping in the decision-making. This work aims to map the areas conducive to the cultivation of coffee species Coffea Arabica L. in the municipality of Caratinga, Minas Gerais. The spatial analysis used data from Mapbiomas, Portal do Café de Minas and IDE-Sisema, information associated with applications of technical and legal restrictions, enabled by the multicriterio analysis of geoprocessing. The result shows that Caratinga has great potential for implantation of new arabica coffee plantations, possessing 38.3% of the territory apt to the grain cultivation. It is concluded that the methods used were able to delimit the potential areas for planting the crop, proving to be an important tool to assist in this type of decision-making.